Application of a method used to deconstruct a single dose pharmacokinetic profile from multiple dose data. (21st April 2015) - Stockmann, Chris; Spigarelli, Michael G.; Healy, Daniel P.; Gottschlich, Michele M.; Kagan, Richard; Balch, Alfred H.; Sherwin, Catherine
Abstract With traditional non‐compartmental methods, it is challenging to deconstruct plasma concentration versus time curves to assess the influence of individual doses. This study describes the application of a mathematical approach used to deconstruct a single dose curve using data derived from the second, third, fourth or nth dosing interval. Using data from a prospective clinical trial it is demonstrated that this approach reliably estimates pharmacokinetic parameters measured following two doses of zolpidem tartrate. Additionally, the study demonstrates the application of this approach using previously published data from a single‐ and multiple‐dose pharmacokinetic study of the antibiotic gatifloxacin. Copyright © 2015 John Wiley & Sons, Ltd.